Effectiveness of a loan recovery programme in a student financial organization : case of higher education loans board - Achola, Fritz Noel Conrad (Strathmore University, 2009)
The financing of higher education in Kenya has been a big challenge to the Government of Kenya, through Higher Education Loans Board (HELB – hereafter referred to as the Board ). There is a growing student population, rising costs of education and an increased dependency by students on financial assistance due to the slow growth of the economy and the impact of poverty levels in the country. This is to be seen against the background of dwindling finances from the Government, who have been the main financers of higher education (Source : Ministry of Education : Budget Estimates) The Board has recognized key challenges that it must put into account in its operations. These challenges include the need for HELB to mobilize funds and become a self-sustaining organization in the long term; increasing demand for loans by Kenyan students, particularly from private and self-sponsored students; the need to maximize the recovery of non-performing loans by entering into strategic partnerships which would assist in the netting of loanees; and the need to reduce the loan default rates. Alternative methods of raising funds urgently need to be looked into by the Board. Secondly, the Board has to deal with the problem of non-performing loans which now stands at 51% (source: HELB database, Loan portfolio analysis) of the outstanding loans. Ways have to b found to find effective ways of reducing the loan repayment default rate. The use of threats and/or incentives to increase long repayment could be the key. Lessons drawn from the banking industry in Kenya can also be used to reduce the loan default rate and the level of non-performing loans. This figure has dropped from a high of 40% in 1999 to 13.83% in 2006. The strategies used by the banks to reduce these figures can be replicated by HELB. The dissertation is therefore an exploratory research on the effectiveness of the Higher Educations Loans Board loan recovery program. The study main objective is to explore methods of improving loan recovery of the student loan scheme. Four research questions have been determined and they relate to the main objective. A review of related literature was conducted, which comprises background of student loan financing, loan default, benchmarking, loan recovery strategies, transformation of microfinance institutions into banks and other literature relating to issues on student loan financing. The gathering of primary data for the research was by use of a questionnaire whereby 40 loanees (ex-university student loan beneficiaries) responded. The propositions that were formulated pointed towards HELB benchmarking itself with banks for improved performance and being eventually transformed into a specialized learner’s bank to finance higher education. Conclusions, implications, limitations and recommendations were completed and statements were made on the findings.
Partial fulfillment for award of Master of Business Administration
Keywords: Bank loans; Banking law--Kenya; Debtor and creditor--Kenya